El estrés y la salud psico-emocional en los estudiantes de la Unidad Educativa Municipal Ciudad de Quevedo - Aguilera Bustamante, Maritza Marisela (2019)
The present investigative work called stress and psycho-emotional health in the students of the municipal educational unit "ciudad de Quevedo" year 2019. With which seeks to improve the psychological health of students, through this research the problem of study is determined its consequences in people and likewise look for coping techniques and fight them. Stress has consequences not only psychological but also physical in the health of people who come to present, causing instability in all areas depending on the type or level of stress of individuals. On the other hand, psycho-emotional health is affected due to external factors such as the contexts in which an individual develops, and internal factors, whether it be a biological or physical illness, this causes the individual to be mentally conditioned, causing psychological emotional imbalance. To treat or control stress and its effects is of vital importance that the person is willing to follow step by step each of the techniques that the psychologist provides and learn to plan their activities to avoid stress with activities and to accumulate work that can later trigger irritability accompanied by other disorders such as anxiety and depression